2021
DOI: 10.3390/ijerph18168635
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Mechanisms and Outcomes among Sub-Saharan African Descendants in Belgium—Contextualizing the HIV Stigma Framework

Abstract: HIV-related stigma and discrimination are recognized barriers to HIV prevention, testing and treatment among people of Sub-Saharan African descent (SSA) origin living in Belgium, but insights into HIV related-stigma mechanisms and outcomes are lacking for this population with high HIV prevalence. Guided by Earnshaw and Chaudoir’s stigma framework (2009), we conducted this qualitative study using 10 focus-groups with 76 SSA community members and 20 in-depth interviews with SSA descendants living with HIV to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Fazeli et al (2017) also reported the intersection between HIV-related discrimination and the internalization of HIV stigma [ 41 ]. The acceptance of what some scholars have termed a ‘spoiled identity’ legitimizes and normalizes internalized HIV stigma which, in this study, were discernible through self-protective tendencies such as self-exclusion, social retraction, avoidance of actions that may unveil ones HIV-positive and risk-taking behaviours such as poor access to HIV health services and suboptimal compliance to ART which have been reported elsewhere [ 42 , 43 ]. A study in Uganda found that the worries about being at an ART clinic and internalized loss of hope due to fear of death were important impediment to same-day ART initiation by female sex workers [ 44 ].…”
Section: Discussionmentioning
confidence: 57%
“…Fazeli et al (2017) also reported the intersection between HIV-related discrimination and the internalization of HIV stigma [ 41 ]. The acceptance of what some scholars have termed a ‘spoiled identity’ legitimizes and normalizes internalized HIV stigma which, in this study, were discernible through self-protective tendencies such as self-exclusion, social retraction, avoidance of actions that may unveil ones HIV-positive and risk-taking behaviours such as poor access to HIV health services and suboptimal compliance to ART which have been reported elsewhere [ 42 , 43 ]. A study in Uganda found that the worries about being at an ART clinic and internalized loss of hope due to fear of death were important impediment to same-day ART initiation by female sex workers [ 44 ].…”
Section: Discussionmentioning
confidence: 57%
“…Hence PrEP could be framed as unnecessary and inducing promiscuity. Previous studies have shown that HIV stigma is indeed high among SSA diaspora communities in Belgium [ 32 , 33 ]. However, our findings also highlight that cultural norms are not as deterministic as may be assumed, as shown by several comments about individual preferences and that once people are properly informed, acceptance will increase.…”
Section: Discussionmentioning
confidence: 99%
“…Using existing prevention structures, PrEP should be presented as a positive sexual health promotion tool [ 38 ], rather than only a risk reduction tool by community-based prevention projects that have already established trustful relationships with diaspora communities. Tailored awareness-raising campaigns should always address the specific knowledge gaps, but should be delivered within a comprehensive and holistic context of HIV de-stigmatization [ 32 , 33 ]. Tailored approaches should be used for specific subgroups, such as LGBTQI+, in collaboration with existing organisations.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may contribute to mental health challenges among PLWH. Internalized shame and worry about the diagnosis, coupled with a lack of comprehensive disease knowledge and stereotypes about HIV, can lead to uncertainty about one's future health, concerns about HIV transmission, and challenges in accessing and maintaining care [9][10][11]. Anticipation of potential stigma and discrimination from others, as well as the actual experiences of enacted stigma and mistreatment, may contribute further to stress, social isolation, and fears around disclosure of one's HIV status [10,12,13].…”
Section: Introductionmentioning
confidence: 99%